THE IMPLEMENTATION OF PROJECT-BASED LEARNING ON DEEP LEARNING - Salwa Desrina; Handi Pabriana; Anisa Septia Megawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Project-Based Learning (PBL) is a learner-centered approach to learning that has the potential to support deep learning through active, collaborative, and contextual learning experiences. However, research on the implementation of PBL in supporting deep learning, as well as teachers’ understanding of the relationship between these two concepts in English language learning, remains limited. This study aims to examine the implementation of Project-Based Learning in supporting Deep Learning and to explore teachers’ understanding of the relationship between PBL and Deep Learning. The study employed a qualitative approach using a case study design at Mutiara Terpadu High School in Palabuhanratu. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were subsequently analyzed using thematic analysis. The research findings indicate that the implementation of PBL supports deep learning through discussions, pair work, group projects, presentations, peer assessment, reflection, and individual assignments, which foster meaningful learning, mindful learning, joyful learning, collaboration, critical thinking, problem-solving, knowledge transfer, reflection, and deep conceptual understanding. In addition, teachers have a comprehensive understanding of the relationship between PBL and Deep Learning, emphasizing the importance of student-centered learning, meaningful learning experiences, the development of higher-order thinking skills, as well as continuous facilitation and reflection. Thus, the implementation of Project-Based Learning contributes to creating meaningful and authentic English language learning that supports the development of Deep Learning.